PERANAN PERSON ORGANIZATION FIT DAN PERSON JOB FIT DALAM MENINGKATKAN JOB SATISFACTION DENGAN WORK ENGAGEMENT SEBAGAI MEDIASI - Ratih Indriyani; Monica Bellinda Sutanto (Fakultas Ekonomi Universitas PGRI Adi Buana, 2021)
Job satisfaction is an important factor in achieving the sales person's self-compatibility with the work environment. Conformity in question is the suitability of individual values ​​with person organization fit and the suitability of individual characteristics person job fit. With this suitability, work engagement will be higher. This study was conducted to analyze the effect of person organization fit and person job fit on job satisfaction through work engagement. This type of research is quantitative research with purposive sampling technique. Research data were collected by distributing questionnaires to all sales persons of PT World Innovative Telecommunication answers to the questionnaire collected as many 220 respondents. The data was processed using partial least squares (PLS) data analysis techniques. The results of the study stated that person organization fit and person job fit had an effect on job satisfaction through work engagement. This proves that work engagement can significantly mediate the effect of person organization fit and person job fit on job satisfaction sales person PT World Innovative Telecommunication.